Nicotine and marijuana attitudes among flavor-only vaping youth: New evidence from Monitoring the Future. (March 2020) - Boccio, Cashen M.; Jackson, Dylan B.; Leal, Wanda E.
Highlights: Flavor-only vaping is not associated with perceived risk and disapproval of traditional tobacco products. Flavor-only vaping is associated with attitudes concerning vaping nicotine. Flavor-only vaping is associated with attitudes concerning marijuana use. Abstract: Background: Vaping has become increasingly popular among youth and young adults in the last decade. At present, very little research has examined how vaping is associated with attitudes concerning the disapproval and perceived risk of using other substances. This paper examines the association between flavor-only vaping and attitudes concerning nicotine and marijuana use in a sample of high school students with no history of nicotine or marijuana use. Methods: We employed negative binomial regression and logistic regression techniques to examine the associations between flavor-only vaping activity and attitudes concerning the risk and disapproval of nicotine and marijuana use utilizing data from the 2017 cohort of Monitoring the Future (MTF). Results: The results suggest that, net of covariates, flavor-only vaping is not significantly associated with attitudes concerning traditional forms of nicotine use. However, flavor-only vaping does appear to be positively and significantly associated with the failure to disapprove and/or perceive the risk of vaping nicotine and regular marijuana use. Conclusions: Flavor-only vaping is positively and significantly associated with the failure to disapprove and/or perceive the risk of vaping nicotine and regular marijuana use.